2013
DOI: 10.1021/ol401653w
|View full text |Cite
|
Sign up to set email alerts
|

Intramolecular Displacement of Phenylselenone by a Hydroxy Group: Stereoselective Synthesis of 2-Substituted Tetrahydrofurans

Abstract: An efficient and stereocontrolled synthesis of 2-substituted tetrahydrofurans has been achieved. The approach employs the asymmetric reduction of γ-phenylseleno ketones obtained by three different procedures that are peculiarly applied to the synthesis of such compounds. Finally, the intramolecular substitution of the phenylselenone residue by the oxygen atom of a hydroxy group gives the tetrahydrofuran ring.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 42 publications
0
26
0
Order By: Relevance
“…For exemple, Minuti et al recently reported a simple synthetic sequence to obtain 2-substituted THF by substitution of a selenone moiety. 73 The enantioselectivity is obtained by a CoreyBakshi-Shibata reduction to form the alcohol, and no erosion of the enantiomeric excess is observed during the cyclization. Similarly to epoxides, oxetanes can be opened by hydroxyl groups.…”
Section: Other Nucleophilic Substitutionsmentioning
confidence: 99%
“…For exemple, Minuti et al recently reported a simple synthetic sequence to obtain 2-substituted THF by substitution of a selenone moiety. 73 The enantioselectivity is obtained by a CoreyBakshi-Shibata reduction to form the alcohol, and no erosion of the enantiomeric excess is observed during the cyclization. Similarly to epoxides, oxetanes can be opened by hydroxyl groups.…”
Section: Other Nucleophilic Substitutionsmentioning
confidence: 99%
“…35a On the basis of HPLC analysis on chiral stationary phase, compound 12b showed the same enantiomeric composition of its precursor 11b, thus supporting that no racemization occurred during the cyclization process. 20 Otherwise, for compound 12a was not possible to obtain a clear separation of the two enantiomers by HPLC.…”
Section: Scheme 3 Synthesis Of 1-substituted Isochromans 12a and 12bmentioning
confidence: 99%
“…19 We recently described the easy and stereoselective preparation of 2-substituted tetrahydrofurans 20 The yield of 5a increased up to 66% when we employed MCPBA in methanol. However, when the oxidation/cyclization of 4a was performed in acetonitrile with an excess of MCPBA and dipotassium hydrogen phosphate, the 2-substituted THP 5a was obtained in excellent yield (80%, Table 2, entry 1) after addition of powdered potassium hydroxide, thus demonstrating that the cyclization step is greatly favourited by polar aprotic solvent.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…epoxides from β-hydroxy phenyl selenides [910], N -benzoyl- and N - tosyl-1,3-oxazolidin-2-ones from β-hydroxyalkyl phenyl selenides [11], N -arenesulfonylazetidines from γ-(phenylseleno)alkyl arylsulfonamides [12], N -acylaziridines [13], 1,3-oxazolines, dihydrooxazine and pyrrolidines from acylamino phenyl selenides [14]. Interestingly, the intramolecular substitution reaction of a phenylselenonyl group was used on enantioenriched γ-hydroxyalkyl phenyl selenides to obtain optically active 2-substituted tetrahydrofurans [15] (see Scheme 2). …”
Section: Introductionmentioning
confidence: 99%